Significantly Improving the Bioefficacy for Rheumatoid Arthritis with Supramolecular Nanoformulations. Issue 16 (17th March 2021) - Ma, Chao; Li, Bo; Zhang, Jinrui; Sun, Yao; Li, Jingjing; Zhou, Hangcheng; Shen, Jianlei; Gu, Rui; Qian, Jiangchao; Fan, Chunhai; Zhang, Hongjie; Liu, Kai
Abstract: As a typical inflammatory disease with chronic pain syndromes, rheumatoid arthritis (RA) generally requires long‐term treatment with frequent injection administration at 1–2 times per day, because common medications such as interleukin1 receptor antagonist (IL1ra) have poor bioavailability and very limited half‐life residence. Here a novel strategy to fabricate nanotherapeutic formulations employing genetically engineered IL1ra protein complexes, yielding ultralong‐lasting bioefficacy is developed rationally. Using rat models, it is shown that these nanotherapeutics significantly improved drug regimen to a single subcutaneous administration in a 14‐day therapy, suggesting their extraordinary bioavailability and ultralong‐acting pharmacokinetics. Specifically, the half‐life and bioavailability of the nanoformulations are boosted to the level of 30 h and by 7 times, respectively, significantly greater than other systems. This new strategy thus holds great promise to potently improve patient compliance in RA therapy, and it can be adapted for other therapies that suffer similar drawbacks. Abstract : A new generation of active nanotherapeutic formulations employing genetically engineered interleukin1 receptor antagonist (IL1ra) protein complexes is developed through a non‐covalent supramolecular assemble approach. Extraordinary bioavailability and ultralong‐acting pharmacokinetics are realized for long‐acting rheumatoid arthritis therapy.